1992
DOI: 10.1080/07399339209515993
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian childbearing couples’ dilemmas and decisions

Abstract: In recent years, an increasing number of lesbian women have chosen to bear children. However, for lesbians, there are many obstacles and unique dilemmas during each phase of the childbearing process. Some of these dilemmas include how to conceive, where to find a health care provider who is sensitive to their concerns, and how to inform family members and friends about the pregnancy and elicit their support. Other dilemmas common to all women are where to give birth and how to assimilate new roles into their l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 6 publications
2
19
0
Order By: Relevance
“…Twenty‐nine of the study participants (83%) were satisfied with their obstetric care whereas the remaining women were disappointed with providers’ uncaring attitudes and lack of knowledge about lesbian health and parenting issues. Similar concerns regarding lesbian biological motherhood were reported by Zeidenstein () and Kenney and Tash ().…”
Section: Literature Reviewsupporting
confidence: 79%
“…Twenty‐nine of the study participants (83%) were satisfied with their obstetric care whereas the remaining women were disappointed with providers’ uncaring attitudes and lack of knowledge about lesbian health and parenting issues. Similar concerns regarding lesbian biological motherhood were reported by Zeidenstein () and Kenney and Tash ().…”
Section: Literature Reviewsupporting
confidence: 79%
“…William's Obstetrics (Cunningham et al, 2001), commonly used by obstetrical residents, is markedly void of any cultural competence material. Lesbian mothers appeared to favor receiving care from lesbian gynecologists and midwives (Kenney and Tash, 1992; Smith et al), but they ultimately desired an HCP who was sensitive, open, and nonjudgmental, willing to listen to the concerns of the prospective parents, and avoided the assumption that all childbearing women were heterosexual (Kenney and Tash, 1992).…”
Section: Disclosure Of Sexual Orientation To Hcpsmentioning
confidence: 99%
“…Historically, lesbians may have had trouble accessing clinic‐based DI due to both legal and ethical/moral arguments against lesbian insemination, and in one older study, researchers reported four women being refused insemination due to their sexual orientation (Harvey et al, 1989). However, lesbian mothers are becoming more visible, and while a large number of women have concerns over the medicalization of conception and the increasing use of high‐tech options for obstetric care (Wajcman, 1991), research revealed that DI was becoming recognized as the method of choice for most couples when choosing an option to facilitate conception of a child (Kenney & Tash, 1992; Lewin, 1993). Olesker and Walsh (1984) reported that eight out of the nine women interviewed chose conception by coitus, with most of the men involved not being informed about the desire for conception.…”
Section: Options For Conceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-insem ination (SI) is technically a relatively straightforw ard procedure and m any lesbians prefer SI to clinic insem ination both because it is cheaper and because it is ® rm ly believed that fresh semen is m ore likely to result in pregnancy than frozen. SI has becom e an established part of lesbian culture (Kenney & Tash, 1993). In Britain in the late 1970s and early 1980s, lesb ians form ed SI groups which investigated the practicalities of SI and wrote m anuals to pass on their knowledge to other wo m en (e.g.…”
Section: The Legislative Background To Si and The Risk Of Hivmentioning
confidence: 99%